Extraction of Bioactive Compounds and Influence of Storage Conditions of Raw Material Chamaenerion angustifolium (L.) Holub Using Different Strategies - Domantas Armonavičius; Mantas Stankevičius; Audrius Maruška (Molecules)
The study evaluates different preparation methods for identifying the best strategy for extracting biologically active compounds from raw Chamaenerion angustifolium (L.) Holub plant material. The methodologies include direct aqueous methanol extraction with a combination of natural aerobic and anaerobic fermentation for 24–72 h, followed by 35 °C and 60 °C drying. Furthermore, the study also focuses on determining the different temperature storage conditions on the stability of biologically active compounds. UV-VIS spectroscopy was used to quantitatively evaluate the total content of phenolic compounds, flavonoids, and radical scavenging activity. For qualitative analysis, chromatographic separation with electrochemical detection (ED) of extracted compounds, a gradient high-performance liquid chromatography (HPLC) system was used. Study results indicate that 48 h natural aerobic fermentation followed by 35 °C drying and 75% (v/v) aqueous methanol extraction yielded the maximum amount of biologically active compounds in Chamaenerion angustifolium (L.) Holub leaves, blossom, and stem samples. Freezing samples in liquid nitrogen had the lowest impact on the total content of phenolic compounds, flavonoids, and radical scavenging activity. HPLC-ED system results identified chlorogenic acid, oenothein B, trans-p-Coumaric acid, ellagic acid, and rutin in Chamaenerion angustifolium (L.) Holub leave samples.